The 'rugged life': Youth and violence in Southern Nigeria - Pratten, D (Routledge, 2007)
This unique volume seeks both to historicize and to deconstruct the pervasive, almost ritualistic, association of Africa with forms of terrorism as well as extreme violence, the latter bordering on and including genocide.